The Association of Down Children - Razzano, Enzo (Medicina e Morale, 2024)
The Down's Children's Association is not a welfare organisation, but for assistance it tries to collaborate as best it can with existing structures; it is instead an organisation for collecting and disseminating information on Down's syndrome (mongolism); for supporting parents, doctors, teachers, social and health workers in general; for promoting studies and research; for continuous updating; for consultancy at all levels. It may also be added that it is currently considered by many to be in the vanguard for the modernity and functionality of its approach.